PERAN UNITED NATION DEVELOPMENT PROGRAM DALAM MEMBANTU PEMERINTAH INDIA MENEKAN ANGKA PENYEBARAN HIV AIDS 2007-2012 - Kuntum Chaira Ummah; Den Yelta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This paper describes the role of the United Nations Development Programme (UNDP) in decline the transmission HIV/AIDS in India 2007-2012. India is the one of developt country and member of UNDP which has serious problem as highest HIV/AIDS suspects in Pacific Asia countries. Human secutiry is one important thing to protect this country from this global epidemi.The data sources used in this research are books, journals, working papers, news from websites and newspaper. To analyze the research question, the writer applies liberal perspective, specifically the Human Security Studies.Human Security Studies argues that security must be provided to society and finally citizens.HIV/AIDS in India have a profound effect on the civilians, especially when influence to family walfare, economic, politic. With the implementation of human security concept and good governance theory, UNDP has helped and protected civilians which way prevention, care and support. UNDP as an organization that focuses on developing for developt country down to help India’s Goverment from HIV/AIDS epidemi.Key word : International Organization, HIV/AIDS, India